The Role Of Social Media In Increasing The Number Of Visits To Batara White House Inn - Merlin Merlin; Abedneigo C. Rambulangi (Universitas Kristen Indonesia Toraja, 2022)
This study aims to find out how the role of social media is to increase the number of occupancy of the Batara White House in Kapala Pitu, toraja utara. This type of research is qualitative. The informants in this study were managers and visitors at Batara White. The results obtained are in increasing the number of occupancy at Batara White House, the management team uses the role of Instagram social media, By using social media from February to May 2023 there has been an increase, namely February with 497 occupancy, March with 693 occupancy, April 867 with occupancy, and in May with 889 occupancy. This happens because there is consistency in uploading Instagram stories and being diligent in reposting posts from other users who come to visit.